Development of multi-objective load shedding optimization via back tracking search algorithm with novel reactive power tracing index - Verayiah R.; Mohamed A.; Shareef H.; Abidin I.H.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power plant loads; Learning algorithms; MATLAB; Multiobjective optimization; Optimization; Reactive power; Back tracking; Backtracking search algorithms; Identification method; Load-shedding; Multi-objective functions; Power flow simulation; System contingencies; Under voltage load shedding; Electric load shedding